Public Administration and Literature - Rixer, Ádám (Public Governance, Administration and Finances Law Review, 2017)
Nowadays Law and Literature courses become more and more popular worldwide; this is also true for Hungary. Examining these attempts, we may conclude that legal problems do reach the students through mainly fictitious literary stories instead of real cases. Accordingly, the idea of Public Administration and Literature courses can be proposed, as well. Among the reasons to introduce such courses we can detect new demands on the side of the students, the need for the methodological renewal of teaching and also the fact that the National University of Public Service already offers MA levels in administrative sciences. This paper – providing several examples – summarizes the main fields and subjects of public administration showed in fine literature and it also collects those genres by which administrative topics are most frequently introduced.